Efficacy and safety of evogliptin monotherapy in patients with type 2 diabetes and moderately elevated glycated haemoglobin levels after diet and exercise. Issue 12 (7th July 2017) - Park, Juri; Park, Sung Woo; Yoon, Kun Ho; Kim, Sung Rae; Ahn, Kyu Jeung; Lee, Jae Hyuk; Mok, Ji Oh; Chung, Choon Hee; Han, Kyung Ah; Koh, Gwan Pyo; Kang, Jun Goo; Lee, Chang Beom; et al.
Abstract : Aims: To evaluate the efficacy and safety of evogliptin, a newly developed dipeptidyl peptidase‐4 inhibitor, in patients with type 2 diabetes (T2D) inadequately controlled by diet and exercise. Materials and Methods: In this randomized, double‐blind, placebo‐controlled, parallel‐group, multicentre, phase III study, 160 patients with T2D were assigned to either evogliptin 5 mg or placebo for 24 weeks. The primary endpoint was the mean change in glycated haemoglobin (HbA1c) from baseline to week 24. Results: The mean baseline HbA1c levels were similar in the evogliptin and the placebo groups (7.20% ± 0.56% vs 7.20% ± 0.63%, respectively). At week 24, evogliptin significantly reduced HbA1c levels from baseline compared with placebo (−0.23% vs 0.05%, respectively, P < .0001). Additionally, the proportion of patients achieving HbA1c <6.5% was significantly higher in the evogliptin group than in the placebo group (33.3% vs 15.2%; P = .008). The overall incidence of adverse events, including hypoglycaemia, was similar in the 2 groups. Conclusions: In this 24‐week study, once‐daily evogliptin monotherapy significantly improved glycaemic control and was well tolerated in patients with T2D.